2021
DOI: 10.3390/brainsci11111472
|View full text |Cite
|
Sign up to set email alerts
|

Effective Connectivity during an Avoidance-Based Pavlovian-to-Instrumental Transfer Task

Abstract: Pavlovian-to-instrumental transfer (PIT) refers to a phenomenon whereby a classically conditioned stimulus (CS) impacts the motivational salience of instrumental behavior. We examined behavioral response patterns and functional magnetic resonance imaging (fMRI) based effective connectivity during an avoidance-based PIT task. Eleven participants (8 females; Mage = 28.2, SD = 2.8, range = 25–32 years) completed the task. Effective connectivity between a priori brain regions engaged during the task was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…A major difference in the experimental implementation of general transfer concerns the use of cues associated with outcomes for which an action was learned (or not) during the instrumental conditioning phase (Table 1). While many authors operationalized general transfer as the capacity of a Pavlovian cue to bias choice toward an outcome that was never obtained through an instrumental action (Table 1: General PIT No−action ) (Nadler et al, 2011;Lewis et al, 2013;Watson et al, 2014;Morris et al, 2015;Claes et al, 2016;Lehner et al, 2016;Garofalo and Robbins, 2017;Quail et al, 2017;Meemken and Horstmann, 2019;Alarcón and Bonardi, 2020b;Hinojosa-Aguayo and González, 2020;Krypotos and Engelhard, 2020;Soutschek et al, 2020;van Timmeren et al, 2020;Petrie et al, 2021), others used a different operationalization of general transfer, where the Pavlovian cue predicted an outcome previously earned by a specific instrumental action, which, however, was no longer available in the transfer phase (Prévost et al, 2012;Garofalo et al, 2019Garofalo et al, , 2020Garofalo et al, , 2021Sennwald et al, 2020; Such a seemingly minor methodological difference actually affects the affordance-like properties of the outcome, i.e., its link with a motor program to obtain the outcome itself. According to some theories (Cisek, 2007), for instance, the presence of a response-outcome link may indeed enhance the motivational value of the outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major difference in the experimental implementation of general transfer concerns the use of cues associated with outcomes for which an action was learned (or not) during the instrumental conditioning phase (Table 1). While many authors operationalized general transfer as the capacity of a Pavlovian cue to bias choice toward an outcome that was never obtained through an instrumental action (Table 1: General PIT No−action ) (Nadler et al, 2011;Lewis et al, 2013;Watson et al, 2014;Morris et al, 2015;Claes et al, 2016;Lehner et al, 2016;Garofalo and Robbins, 2017;Quail et al, 2017;Meemken and Horstmann, 2019;Alarcón and Bonardi, 2020b;Hinojosa-Aguayo and González, 2020;Krypotos and Engelhard, 2020;Soutschek et al, 2020;van Timmeren et al, 2020;Petrie et al, 2021), others used a different operationalization of general transfer, where the Pavlovian cue predicted an outcome previously earned by a specific instrumental action, which, however, was no longer available in the transfer phase (Prévost et al, 2012;Garofalo et al, 2019Garofalo et al, , 2020Garofalo et al, , 2021Sennwald et al, 2020; Such a seemingly minor methodological difference actually affects the affordance-like properties of the outcome, i.e., its link with a motor program to obtain the outcome itself. According to some theories (Cisek, 2007), for instance, the presence of a response-outcome link may indeed enhance the motivational value of the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the findings on human general transfer have been quite heterogeneous. For instance, while some studies report evidence for general transfer using response rate as a dependent variable ( Lewis et al, 2013 ; Quail et al, 2017 ; Alarcón and Bonardi, 2020b ), others failed to observe it ( Meemken and Horstmann, 2019 ; Petrie et al, 2021 ), or found it only in aversive conditions ( Nadler et al, 2011 ), or using vigor as a dependent variable ( Watson et al, 2014 ; Garofalo and Robbins, 2017 ). Such heterogeneity in results may be at least partially explained by the lack of studies directly investigating this general transfer effect.…”
Section: Introductionmentioning
confidence: 99%